2017
DOI: 10.1007/s10236-017-1089-5
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the mesoscale variability in global ocean eddy-permitting numerical systems

Abstract: The role of data assimilation procedures on representing ocean mesoscale variability is assessed by applying eddy statistics to a state-of-the-art global ocean reanalysis (C-GLORS), a free global ocean simulation (performed with the NEMO system) and an observation-based dataset (ARMOR3D) used as an independent benchmark. Numerical results are computed on a 1/4 • horizontal grid (ORCA025) and share the same resolution with ARMOR3D dataset. This "eddy-permitting" resolution is sufficient to allow ocean eddies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…The present reanalysis shows some improvements as compared to predecessors as discussed and validated in Storto and Masina (2016). Recently, Cipollone et al (2017) show that data assimilation enhances and corrects mesoscale variability on a wide range of features that cannot be well simulated by the free simulation. Comparisons with observations show that the "eddy-permitting" resolution is sufficient to allow ocean eddies to form and the assimilation recovers most of the missing turbulence as observed by satellite products.…”
Section: Global Surface Ocean Currentssupporting
confidence: 51%
See 1 more Smart Citation
“…The present reanalysis shows some improvements as compared to predecessors as discussed and validated in Storto and Masina (2016). Recently, Cipollone et al (2017) show that data assimilation enhances and corrects mesoscale variability on a wide range of features that cannot be well simulated by the free simulation. Comparisons with observations show that the "eddy-permitting" resolution is sufficient to allow ocean eddies to form and the assimilation recovers most of the missing turbulence as observed by satellite products.…”
Section: Global Surface Ocean Currentssupporting
confidence: 51%
“…The reanalysis spans 1979-2013, but we focused on the 1985-2013 period when the assimilation uses the daily satellite sea-surface temperature supplied by National Oceanic and Atmospheric Administration (Reynolds et al, 2007) and along-track altimetric observations provided by AVISO. Recently, Cipollone et al (2017) show that data assimilation enhances and corrects mesoscale variability on a wide range of features that cannot be well simulated by the free simulation. The present reanalysis shows some improvements as compared to predecessors as discussed and validated in Storto and Masina (2016).…”
Section: Global Surface Ocean Currentsmentioning
confidence: 99%
“…Others have compared those properties with other ocean variables (e.g., ocean color; Gaube et al, ; Kobayashi et al, ; Zhang et al, ) to relate spatial and temporal patterns. And others use the altimetry estimates of the eddy field to validate or constrain ocean models (Cipollone et al, ; Nagai et al, ). In all those cases the results should be analyzed with caution as they are based on a biased characterization of the eddy field: Most of the actual eddy field is missed and the part that could be correctly captured suffer from aliasing and noise.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that during strong northerly storms, the bottom currents are dominated by wave-induced velocities while direct wind-induced currents are smaller. Cipollone et al (2017) compared three global ocean products: global reanalysis (C-GLORES), observed global data set (ARMOR3D), and a free running Beddy-permitting^global ocean model (NEMO). The goal was to evaluate data assimilation schemes and see how well these systems can represent mesoscale variability in the ocean.…”
mentioning
confidence: 99%
“…The papers can be generally divided into four categories: (1.) Model development, analysis, and data assimilation (Byun and Hart 2017;Cipollone et al 2017, Jordi et al 2017Liu et al 2017;Wei et al 2017); (2.) Coastal modeling and process studies (Bie et al 2017;Ezer 2017;Ezer and Atkinson 2017;Liao et al 2017;Lu et al 2017, Trotta et al 2017; (3.)…”
mentioning
confidence: 99%